2019
DOI: 10.5039/agraria.v14i2a5645
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physicochemical descriptors for characterization of mangaba tree germplasm

Abstract: The objective of this study was to evaluate and select morphological and physicochemical descriptors for the characterization of mangaba tree germplasm. We used 30 descriptors in 54 plants from 10 accesses in the fruiting stage (CA, AB, PT, PR, TC, PA, LG, BI, IP and AD) from the Active Germplasm Bank of Embrapa Coastal Tablelands located in the Experimental Field of Itaporanga d'Ajuda, Sergipe, Brazil, faithful trustee of the species. The diversity was verified between and within the accesses, however, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
4
4
1
2
Order By: Relevance
“…In this study, the predominant fruit shape observed in the accessions was spheroid (Table 4). Muniz et al (2019) and Oliveira, Silva and Chagas (2018) reported 2018) observed the mean fruit weight of 31.94 g, values above those found in fruits from Embrapa Tabuleiros Costeiros Mangaba Genebank (19.38 g). Regarding seed physical attributes, Muniz et al (2019) reported similar values to those found in this study for the number of seed, however, the weight of seeds was higher.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In this study, the predominant fruit shape observed in the accessions was spheroid (Table 4). Muniz et al (2019) and Oliveira, Silva and Chagas (2018) reported 2018) observed the mean fruit weight of 31.94 g, values above those found in fruits from Embrapa Tabuleiros Costeiros Mangaba Genebank (19.38 g). Regarding seed physical attributes, Muniz et al (2019) reported similar values to those found in this study for the number of seed, however, the weight of seeds was higher.…”
Section: Resultsmentioning
confidence: 76%
“…Photos Josue ´Francisco da Silva Ju ´nior width, thickness, and volume) were evaluated. The following physicochemical attributes were also evaluated: (a) pulp pH, performed with an electronic potentiometer using five grams of pulp diluted in 50 mL of distilled water; (b) Titratable Total Acidity (TTA), determined by titration with 0.1 N NaOH solution and 1% phenolphthalein as indicator, and the values expressed as a citric acid percentage; (c) soluble solids content (SS), using a digital refractometer, PAL-1 AtagoÒ, according to AOAC (1992), and the contents expressed as °Brix; (d) SS / TTA, soluble solids / Titratable Total Acidity ratio; (e) Vitamin C (Muniz et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…O fruto de mangaba possui tamanho, forma e cores variadas, geralmente elipsoidal ou arredondada, amarelada ou esverdeada com pigmentação vermelha ou sem pigmentação (Vieira et al, 2010, Ferro et al, 2015. Esses resultados corroboram com vários estudos para as populações do Nordeste e Centro Oeste do Brasil com valores aproximados entre 31,12 mm e 38,78 mm (Moura et al, 2002;Ganga et al, 2010;Freitas, 2012;Nascimento et al, 2014;Ferro et al, 2015;Perfeito et al, 2015;Freitas, 2012;Vieira et al, 2017;Nunes, 2018;Pinheiro et al, 2018;Santos et al, 2018;Muniz et al, 2019). Valores superiores aos encontrados neste estudo foram de Vieira (2011), para os estados de Goiás e Mato Grosso com valores médios de comprimento, largura e massa fresca de 44,7mm, 40,1mm e 42,7g; e 44,57mm, 41,59 mm e 46,49 g.…”
Section: Morfometria De Frutounclassified
“…Para o número médio de sementes por fruto foram inferiores aos encontrados por Moura et al (2002), Ganga et al (2010), Vieira (2011), Freitas, (2012, Gonçalves et al (2013), Nunes (2018) e Muniz et al (2019). E semelhantes aos valores de Lúcio et al (2019) e Zuffo et al (2019), com valores de 5,77 e 4,14.…”
Section: Morfometria De Frutounclassified
“…Other intrinsic factors that affect this species' conservation are the recalcitrant character of the seeds and the di culties of its micropropagation. Thus, the germplasm of H. speciosa has been conserved as live plants kept in situ, in permanent preservation areas, legal reserves, conservation units, and in germplasm collections maintained by Federal University of Goiás (Ganga, Chaves, and Naves, 2009), Embrapa Amapá (Yokomizo, Santos and Freitas, 2017), State Agricultural Research Corporation of Paraíba (Souza et al, 2007), and Embrapa Tabuleiros Costeiros in Sergipe (Muniz et al, 2019), that are susceptible to human actions, climate change and natural disasters.…”
Section: Introductionmentioning
confidence: 99%